Classical quantum mechanics – particle is the pulse of matter waves - Michopoulos, Dimosthenis (Open Science Journal, 2020)
Since the very first development of Quantum Mechanics there are many scientists who, despite the fact that everything seems to work perfectly and the experimental results verify the theoretical predictions, do not understand what is really going on. That is why there are many different interpretations of this subject nowadays. This paper provides a new interpretation, aiming to illustrate the fact that Quantum Mechanics is actually an extension of Classical Physics, and in contrast to other interpretations we illustrate a possible experimental verification of theoretical wording.